The Estimation of Phenotypic and Genetic Parameters for Growth Rate Traits of Abergelle Goat Under the Community‐Based Breeding Programme in the North‐Eastern Parts of Ethiopia - Yeshiwas Walle Abebe; Wossenie Shibabaw Meberatie; Zeleke Tesema Wondie (Veterinary Medicine and Science, 2026)
ABSTRACT Background Understanding phenotypic performance and genetic parameter estimation is important for effective genetic progress in animal breeding and genetics. The data were collected for 6 years (2018–2023) from the established village of Abergelle goat community‐based breeding programme (CBBP) area in Sekota Dryland Agricultural Research Center. The investigated traits were birth weight (BWT), 3‐month weight (TMWT), 6‐month weight (SMWT), 9‐month weight (NMWT), yearling weight (YWT), average daily weight gain from birth to 3 months (ADG1), average daily weight gain from 3 to 6 months (ADG2), average daily weight gain from 6 to 9 months (ADG3) and average daily weight gain from 9 months up to yearling age (ADG4). Objectives To evaluate the phenotypic performance and genetic parameter estimation of growth rate traits of Abergelle goat breeds in CBBP in scale‐up villages in north‐eastern parts of Ethiopia. Methods Four univariate animal models were fitted using the average information restricted maximum likelihood (AI‐REML) procedure to estimate variance components. Results The overall least square mean (LSM) ± standard error (SE) of ADG1, ADG2, ADG3 and ADG4 were 58.2 ± 2.27, 37.8 ± 2.04, 19.2 ± 0.7 and 10.5 ± 0.12 g per day, respectively. The direct heritability estimates for BWT, TMWT, SMWT, NMWT, YWT, ADG1, ADG2, ADG3 and ADG4 were 0.34 ± 0.070, 0.45 ± 0.062, 0.40 ± 0.040, 0.42 ± 0.07, 0.41 ± 0.14, 0.18 ± 0.04, 0.03 ± 0.001, 0.19 ± 0.04 and 0.19 ± 0.04, respectively. Genetic correlations among BWT, TMWT, SMWT, NMWT and YWT were in the range of 0.068–0.84 and phenotypic correlations were also in the range of 0.23–0.89. Genetic correlations for BWT was moderate and higher among SMWT, NMWT and YWT, indicating correlated responses. Thus, BWT had no strong link to later growth in Abergelle goats under CBBP scale‐up village. Conclusion The moderate to high direct heritability estimates indicate that selection for growth would be effective in achieving genetic improvement.